Coronary-Cameral Fistula Connecting the Left Anterior Descending Artery and the First Obtuse Marginal Artery to the Left Ventricle: A Rare Finding - Abdul Mannan Khan Minhas; Ehtesham Ul Haq; Ahmed Arslan Yousuf Awan; Arshad Ameer Khan; Ghazanfar Qureshi; Pragathi Balakrishna (Case Reports in Cardiology)
Coronary-cameral fistulas are rare congenital malformations, often incidentally found during cardiac catheterizations. The majority of these fistulas are congenital in nature but can be acquired secondary to trauma or invasive cardiac procedures. These fistulas most commonly originate in the right coronary artery and terminate into the right ventricle and least frequently drain into the left ventricle. Depending upon their size and location, coronary-cameral fistulas can lead to congestive heart failure, myocardial infarction, and bacterial endocarditis. We describe a case of 49-year-old woman who presented with worsening exertional dyspnea and leg swelling. Transthoracic echocardiogram revealed an ejection fraction of 35%. Cardiac catheterization demonstrated a fistula connecting the left anterior descending artery and the first obtuse marginal artery to the left ventricle. In this report, the authors provide a concise review on coronary fistulas, complications, and management options.